Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd007160.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy for acute myocardial infarction

Abstract: There is no conclusive evidence from randomised controlled trials to support the routine use of inhaled oxygen in people with AMI. A definitive randomised controlled trial is urgently required, given the mismatch between trial evidence suggestive of possible harm from routine oxygen use and recommendations for its use in clinical practice guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…16,17 McNulty et al 4 showed that breathing supplemental oxygen for 15 minutes with a mask increases coronary vascular resistance by 40% and decreases Doppler flow velocity by 20% and coronary blood flow by 30% in patients undergoing cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 McNulty et al 4 showed that breathing supplemental oxygen for 15 minutes with a mask increases coronary vascular resistance by 40% and decreases Doppler flow velocity by 20% and coronary blood flow by 30% in patients undergoing cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…Sublingual nitrates are also commonly used. There is no clear consensus, despite meta-analysis, on whether oxygen should be delivered in acute MI93 but it is likely to be of use in those who are breathless, hypoxic or who have heart failure. A 300 mg chewed loading dose of aspirin should be offered to the patient as long as there are no contraindications 94 95.…”
Section: Acs On Operationsmentioning
confidence: 99%
“…6 More recent studies have called this routine practice into question, with a similar signal toward more negative outcomes. 7 Adverse physiological effects of supplemental oxygen related to increasing coronary vascular resistance and generation of reactive oxygen species have been described, 8,9 fueling the need for an adequately powered randomized, clinical trial. 7 In this issue of Circulation, Stub and colleagues 10 sought to determine the relationship between supplemental oxygen compared with no oxygen therapy with infarct size in normoxic patients with STEMI undergoing primary PCI within the Air Versus Oxygen Myocardial Infarction (AVOID) study.…”
Section: Article See P 2143mentioning
confidence: 99%
“…7 Adverse physiological effects of supplemental oxygen related to increasing coronary vascular resistance and generation of reactive oxygen species have been described, 8,9 fueling the need for an adequately powered randomized, clinical trial. 7 In this issue of Circulation, Stub and colleagues 10 sought to determine the relationship between supplemental oxygen compared with no oxygen therapy with infarct size in normoxic patients with STEMI undergoing primary PCI within the Air Versus Oxygen Myocardial Infarction (AVOID) study. Accordingly, 638 patients with suspected STEMI were enrolled in the field by paramedics serving 9 metropolitan hospitals in Melbourne, Australia, between October 2011 and July 2014, of whom 441 had confirmed STEMI.…”
Section: Article See P 2143mentioning
confidence: 99%